Significantly worse isokinetic hamstring-quadriceps ratio in patellofemoral compared to condylar defects 4 years after autologous chondrocyte implantation - Müller, Sebastian; Beckmann, Nicholas A. (Knee surgery, sports traumatology, arthroscopy, 2015)
Purpose Detailed biomechanical analysis including isokinetic muscle strength measurements after autologous chondrocyte implantation (ACI) are still rare, but might be of crucial importance for long-term outcomes. The present prospective study was performed to evaluate whether defect location had any influence on clinical and biomechanical outcomes 4 years after ACI.MethodsForty-four patients with full-thickness cartilage defects ICRS grade III B and C underwent ACI and were assigned to two groups, the femoral condyle group or the patellofemoral joint group. Clinical scores were gathered preoperatively and 6, 12 and 48 months after implantation using the International Knee Documentation Committee (IKDC) score and the International Cartilage Repair Society (ICRS) form. Isokinetic strength measurements were performed 48 months postoperatively comparing healthy and operated knee joint of each patient.ResultsClinical scores (ICRS, IKDC) showed continuous significant (p < 0.05) improvement over the study period for both groups. Isokinetic muscle strength measurements showed significantly reduced maximum strength capacities for the operated knee joint compared to the healthy knee in both groups (p < 0.05). Hamstring-quadriceps ratios of the operated extremity revealed a significant change in physiological muscle balancing (ratios >1.0) based on significantly impaired extensor muscle strength in the patellofemoral joint group.ConclusionAll patients showed significant strength deficits on the operated extremity 4 years after ACI. Furthermore, the patellofemoral compartment in particular showed significantly worse hamstring-quadriceps ratios compared to condylar defects. Consequently, more efforts should be made to restore muscular strength especially of the quadriceps and the rehabilitation protocol should be adjusted accordingly.Level of evidenceII.
Gesehen am 21.02.2017